2019
DOI: 10.1177/1091581818824313
|View full text |Cite
|
Sign up to set email alerts
|

CDER Experience With Juvenile Animal Studies for CNS Drugs

Abstract: A survey was undertaken to evaluate juvenile animal studies conducted for drug applications reviewed by the Center for Drug Evaluation and Research between 2009 and 2014. Some conclusions about the nonclinical pediatric safety assessment based on studies performed in support of central nervous system–active compounds are presented here. A total of 44 completed studies from 32 New Drug Applications submitted to the Divisions of Psychiatry and Neurology Products were evaluated. Data on animal species and age ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…The incidence of positive findings in our project is also roughly consistent with recently published data from a similar research project conducted by the FDA Divisions on Psychiatry and Neurology Drugs, 25 particularly the low incidence of positive findings for the FOB. Effects were observed during off-treatment for 5 of 14 drugs, that is, in 36% of the studies, compared to the 54% reported by FDA Divisions just mentioned.…”
Section: Behavioral Examinations (Rat Studies)supporting
confidence: 90%
“…The incidence of positive findings in our project is also roughly consistent with recently published data from a similar research project conducted by the FDA Divisions on Psychiatry and Neurology Drugs, 25 particularly the low incidence of positive findings for the FOB. Effects were observed during off-treatment for 5 of 14 drugs, that is, in 36% of the studies, compared to the 54% reported by FDA Divisions just mentioned.…”
Section: Behavioral Examinations (Rat Studies)supporting
confidence: 90%
“…In part this is why neurotoxicity assessments often rely on behavioral evidence along with neuropathological and/or neurochemical evidence (Bolon et al, 2011). Another reason behavioral assessment is used is because it represents the integrated output of the brain and is often a sensitive index of whether a significant effect on brain function has occurred (Piersma et al, 2012;Foster, 2014;Fisher et al, 2019). These factors, together with the fact that most of the human data are behavioral has led to behavior being a major component of developmental neurotoxicity testing (DNT) assessments.…”
Section: Introductionmentioning
confidence: 99%
“…A juvenile toxicity study is likely warranted if damage is anticipated in one or many developing organs, 9,10,30 of which the nervous system is a principal target. 31 The CNS (and particularly the brain) of developing animals and humans is known to be targeted by certain small molecule classes including ethanol, 32,33 anesthetics (eg, isoflurane, ketamine, and other N-methyl-D-aspartate receptor antagonists), 11,34 antiepileptics (eg, phenytoin, sodium valproate, vigabatrin), 11,[35][36][37] antineoplastic chemotherapies, 38,39 retinoids, 36 and stimulants (eg, caffeine, methamphetamine) 36,40 as well as many environmental contaminants (chemicals and metals) [41][42][43] and various endogenous metabolites. 33 Neurodevelopmental effects of such agents depend on the developmental age of exposure.…”
Section: Neurobiological Factors Influencing the Design Of Juvenile Toxicity Studiesmentioning
confidence: 99%
“…Given that developmental processes associated with the immature CNS differentially affect the pharmacokinetics and pharmacodynamics of xenobiotics, [72][73][74][75] the neurotoxic potential of a pharmaceutical candidate is a major consideration in making such weight-of-evidence decisions. 5,31 Guidance for pharmaceutical development by regulatory agencies (eg, the US Food and Drug Administration [FDA] 8 ) or global consortia to standardize safety assessment methods for new medical products (eg, the International Council for Harmonisation of Technical Requirements for Pharmaceuticals Image of a Multibrain preparation showing multiple young adult rat brains coembedded and simultaneously sectioned to produce highly homologous coronal brain sections to permit morphometric measurements on the hippocampus or on other neuroanatomic structures at this level of the brain. This anatomic orientation conforms to current STP "best practice" recommendations for the quantitative analysis portion of conventional developmental neurotoxicity studies (DNTS) in rats.…”
Section: Juvenile Animal Studies For Pediatric Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation